Improving Quality Of The Services In Manet Usign The Hierarchical Fair Service Curve And Fisheye State Routing Protocol (International Journal of Engineering and Computer Science, 2016)
Mobile Ad-hoc networks (MANET) is one of the self configuring and infrastructure less connected wireless networks, which consists of the end hosts and routers. The main issue in the Mobile Ad-hoc networks is a bandwidth aware queue management and quality of the services while sharing the packets in the network. These challenges are increasing the traffic in the real time applications, consumes energy in the MANET. So, the proposed system improves the Quality of the Service (QoS) by applying the Hiearchical Fair Service Curve (HFSC) packet scheduling algorithm and the Fisheye State Routing protocol. The proposed algorithm uses the link-sharing services scheme to maintain the real time application with high quality of services, less delay and high throughput. Thus the of the proposed system is implemented in the NS2 simulation tool and the performance is evaluated with the help of the performance metrics such as, Average delay, Average throughput, Routing overhead, Packet delivery ratio